Denote by [tex]Y(s)[/tex] the Laplace transform of [tex]y(t)[/tex].
[tex]y''-3y'+2y=4t-6[/tex]
Take the Laplace transform of both sides:
[tex](s^2Y(s)-sy(0)-y'(0))-3(sY(s)-y(0))+2Y(s)=\dfrac4{s^2}-\dfrac6s[/tex]
Solve for [tex]Y(s)[/tex]:
[tex](s^2Y(s)-s-2)-3(sY(s)-1)+2Y(s)=\dfrac4{s^2}-\dfrac6s[/tex]
[tex](s^2-3s+2)Y(s)=\dfrac4{s^2}-\dfrac6s+s-1[/tex]
[tex]Y(s)=\dfrac{4-6s-s^2+s^3}{s^2(s^2-3s+2)}[/tex]
[tex]Y(s)=\dfrac{4-6s-s^2+s^3}{s^2(s-1)(s-2)}[/tex]
Decompose the right side into partial fractions: we're looking for constants [tex]a_1,\ldots,a_4[/tex] such that
[tex]\dfrac{4-6s-s^2+s^3}{s^2(s-1)(s-2)}=\dfrac{a_1}s+\dfrac{a_2}{s^2}+\dfrac{a_3}{s-1}+\dfrac{a_4}{s-2}[/tex]
[tex]4-6s-s^2+s^3=a_1s(s-1)(s-2)+a_2(s-1)(s-2)+a_3s^2(s-2)+a_4s^2(s-1)[/tex]
Expanding on the right side gives
[tex]2a_2+(2a_1-3a_2)s-(3a_1-a_2+2a_3+a_4)s^2+(a_1+a_3+a_4)s^3[/tex]
and matching up coefficients gives the system
[tex]\begin{cases}2a_2=4\\2a_1-3a_2=-6\\3a_1-a_2+2a_3+a_4=1\\a_1+a_3+a_4=1\end{cases}\implies a_1=0,a_2=2,a_3=2,a_4=-1[/tex]
So we have
[tex]Y(s)=\dfrac2{s^2}+\dfrac2{s-1}-\dfrac1{s-2}[/tex]
and taking the inverse transform of both sides is trivial, giving
[tex]\boxed{y(t)=2t+2e^t-e^{2t}}[/tex]